Study on a Controlled Splitting Scheme Based on Layer Expanding Graph Algorithm - Wang, Yi Fei; Liao, Qing Fen; Yang, Jian; Tang, Fei (Applied Mechanics and Materials, 2014)
Optimal controlled splitting is an emergency strategy to split the power system into several sub-regions based on global electrical information before the collapse of the system which is subject to severe disturbances. How to seek the optimal splitting sections rapidly and accurately is a key problem in controlled splitting field. A controlled splitting scheme based on layer expanding graph algorithm is presented in this paper. Firstly, source nodes of island regions extend out for the formation of the island regions. Secondly, island regions can be combined to make up synchronous sub-regions on the basis of the clustering of generators. At last, the optimal sections can be determined according to the initial and improved adjustment of splitting sections. Moreover, the scheme proposed can be adapt to the change of operation mode of the power system. The accuracy and effectiveness of the scheme is shown by the simulation results of CEPRI 36-bus system.